Prospective efficient ambient energy harvesting sources for iot-equipped sensor applications - Mishu M.K.; Rokonuzzaman M.; Pasupuleti J.; Shakeri M.; Rahman K.S.; Hamid F.A.; Tiong S.K.; Amin N. (MDPI AG, 2023)
In the past few years, the internet of things (IoT) has garnered a lot of attention owing to its significant deployment for fulfilling the global demand. It has been seen that power-efficient devices such as sensors and IoT play a significant role in our regular lives. However, the popularity of IoT sensors and low-power electronic devices is limited due to the lower lifetime of various energy resources which are needed for powering the sensors over time. For overcoming this issue, it is important to design and develop better, high-performing, and effective energy harvesting systems. In this article, different types of ambient energy harvesting systems which can power IoT-enabled sensors, as well as wireless sensor networks (WSNs), are reviewed. Various energy harvesting models which can increase the sustainability of the energy supply required for IoT devices are also discussed. Furthermore, the challenges which need to be overcome to make IoT-enabled sensors more durable, reliable, energy-efficient, and economical are identified. 2020 by the authors. Licensee MDPI, Basel, Switzerland.